The Development of E-Puzzle Learning Media on the Bhinneka Tunggal Ika Topic in Shaping the Profile of Pancasila Students in Grade X of MAN 1 Banyumas - Apriana Nurlaeli; Wildan Nurul Fajar; Elly Hasan Sadeli (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to develop e-puzzle learning media for the "Bhinneka Tunggal Ika" topic and to assess the feasibility of using this e-puzzle learning media to shape the profile of Pancasila students in grade X at MAN 1 Banyumas. The research method used in this study is Research and Development (RnD) with the Borg and Gall development model. The sample consists of class X-13. Data collection techniques include observation, interviews, questionnaires, pretests, and post-tests. Data analysis includes validation analysis, practicality analysis, and effectiveness analysis of the media. Based on the research, the development of e-puzzle learning media for the "Bhinneka Tunggal Ika" topic to shape the profile of Pancasila students is deemed suitable for use as a learning media. This is demonstrated by increased knowledge acquisition, with an average pretest score of 62.2% and an average post-test score of 88.4%. The validity and practicality test results have an overall average of 83.81%, indicating a highly feasible category. The effectiveness test also yielded a 100% learning achievement rate, categorized as highly effective. The calculation of N-gain indicates an increase in learning outcomes, with a score of 0.70, categorized as high.